Highly Improved Switching Properties in Flexible Aluminum Oxide Resistive Memories Based on a Multilayer Device Structure. (20th September 2018) - Jang, Jingon; Choi, Han‐Hyeong; Paik, Sung Hoon; Kim, Jai Kyeong; Chung, Seungjun; Park, Jong Hyuk
Abstract: Multilayer aluminum oxide (Al2 O3 ) resistive memory devices, exhibiting robust switching properties fabricated on a flexible polyethylene naphthalate substrate using only physical vapor deposition methods at room temperature, are reported here. Improved reliability and robust switching properties of the multilayer Al2 O3 memory devices are observed compared to those of the single‐layer devices, with the assistance of a guide filament formed in the bottom Al2 O3 resistive layer. The multilayer Al2 O3 resistive memory devices exhibit nonvolatile and bipolar resistive switching properties with high ON/OFF ratio (>10 4 ), DC sweep endurance cycles (>700), statistical uniformity, and retention times (2 × 10 4 s). The role of the guide filament in the multilayer structure is identified in the non‐rewritable properties of the bottom layer device, increased reset current values, and spatial temperature distribution simulation. Thus, the formation sites of the switchable filament in the top Al2 O3 layer can be specified by the guide filament, resulting in remarkable improvement of reproducibility with more robust metallic percolation paths. The reliable resistive switching properties in flexible conditions is also evaluated in a bent radius of 10 mm, and the suggested flexible multilayer memory devices can provide promising strategies to be utilized in future practical storage media. Abstract : The effect of multilayer structure in aluminum oxide resistive memory devices is studied in terms of filamentary conduction with enhanced resistive switching properties. The multilayer memory devices present nonvolatile and bipolar switching properties, and exhibit high reproducibility over 30 times compared to the single‐layer devices through concentrated multiple metallic filament transport.